Culdoscopy in gynecology and infertility - Hoyla Cox, Javier (2015)
The Culdoscopy is a step forward so rough path of accurate diagnosis of diseases of the genital tract. Sometimes it is difficult, almost impossible, to ensure the nature of the condition by regular gynecological, such as the history, the bimanual examination and ancillary radiologic procedures including analysis; It is where comes into play major role direct visual examination of the internal genitalia, through Culdoscopy, also called transvaginal Pelvioscopía or Doulascopía.